Serum symmetric dimethylarginine and creatinine in Birman cats compared with cats of other breeds. Issue 10 (October 2018) - Paltrinieri, Saverio; Giraldi, Marco; Prolo, Amanda; Scarpa, Paola; Piseddu, Eleonora; Beccati, Massimo; Graziani, Benedetta; Bo, Stefano
Objectives: The aim of this study was to assess whether, in contrast to serum creatinine, which is higher in Birman cats than in other breeds, the serum concentration of symmetric dimethylarginine (SDMA) is comparable in clinically healthy Birmans and in the general feline population. This could allow, in this breed, to better evaluate chronic kidney disease (CKD). Methods: Serum creatinine and SDMA were measured in clinically healthy Birmans (n = 50) and in cats of other breeds (n = 46), and the results were statistically compared. A breed-specific reference interval (RI) was established for Birmans and compared with the RI for the general feline population (0.0–14.0 µg/dl). Results: Creatinine (1.58 ± 0.36 mg/dl) and SDMA (12.2 ± 2.8 µg/dl) were higher ( P <0.001) in Birmans than in cats of other breeds (1.19 ± 0.17 mg/dl; 10.3 ± 2.5 µg/dl). In 20/50 Birman cats (40.0%) serum creatinine was higher than both the non-breed-specific RI of our laboratory and the threshold recommended to classify cats as IRIS stage 2 (1.6 mg/dl). The concentration of SDMA was higher than the pre-existing RI in 10/50 Birmans (20.0%) and in four cats of other breeds (8.7%). Among Birmans, the proportion of cats with SDMA >14 µg/dl was lower ( P <0.017) than the proportion of cats with creatinine >1.60 mg/dl. However, the deviation from the upper limit of the RI was lower than the analytical variability of the method in 7/10 Birmans and in 4/4 cats of other breeds. The breed-specific RI (3.5–18.7 µg/dl) overlapped with the pre-existing one. Conclusions and relevance: SDMA may be a better marker of CKD in Birman cats than creatinine when non-breed-specific RIs are utilised. The coupled analysis of creatinine and SDMA could help prevent errors in diagnosing and staging CKD in Birman cats.